Changing Livelihood Strategies in a Conservation Area: Fishers, Farmers, and Sand Mining in Merauke, Indonesia - Untari, Untari; Darma, Rahim; Betaubun, Philipus; Arief, Andi Adri; Fudjaja, Letty (Forest and Society, 2022)
The Wasur National Park (WNP) includes the Ramsar Site, an important area for global conservation efforts in wetlands. This coastal area also supports the socio-economic activities of local and non-local communities who are highly dependent on natural resources. Conservation efforts in the area are sometimes at odds with the sustainability of local livelihoods and poverty alleviation initiatives for the community. The aim of this study is to describe the sources of community livelihoods in the Wasur Naukenjerai National Park area, specifically around agricultural, fisheries, and sand mining dynamics. Using a qualitative research design, this study uses a field survey to collect primary data sourced from key informants with in-depth interviews from 15 community respondents in three sample villages on the coast, and seven key informants from relevant government agencies. The results show that the main livelihood source for people in the protected area are as fishermen and farmers. Sand mining has emerged as an alternative source of livelihood but has caused degradation of beaches and land in the Wasur National Park area. In addition, there are activities of buying and selling agricultural land in protected areas. The protection of the rights of the community in the area and government support programs have been unable to guarantee the welfare of the community. For this reason, it is necessary to strengthen and further support local institutions livelihoods to ensure the sustainability of Wasur National Park area management.